From Surface Learning to Deep Understanding: Interactive Media as A Means of Strengthening Elementary Students’ Critical Thinking - Sri Nur Rahmi; Wahidmurni; Samsul Susilawati (Edudeena : Journal of Islamic Religious Education, 2026)
Digital transformation has created opportunities for integrating interactive media into learning processes. However, instructional practices in elementary schools remain largely surface-oriented and have not yet optimally fostered deep understanding or students’ critical thinking skills. Empirical investigation is therefore required to explore the role of interactive media as a catalyst for the transition toward meaningful learning. This study aims to analyze the role of interactive media in strengthening elementary school students’ critical thinking skills through deep learning processes. This quantitative study employed an explanatory survey design involving 680 elementary school teachers as respondents. Data were collected through a Likert-scale questionnaire measuring three reflective constructs: Interactive Media, Deep Learning, and Critical Thinking. Data analysis was conducted using SmartPLS 4. The data, obtained from elementary school teachers through a five-point Likert-scale questionnaire, captured information on the use of interactive media, deep learning practices, and students’ critical thinking skills. Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to examine both direct and indirect relationships among the variables. The findings indicate that the use of interactive media has a significant effect on deep learning. Deep learning was also found to have a significant effect on students’ critical thinking skills. Furthermore, deep learning serves as a significant mediator in the relationship between the use of interactive media and students’ critical thinking skills. These findings suggest that the effectiveness of interactive media in learning is determined not merely by the intensity of its use, but by its capacity to facilitate reflective, analytical, and meaningful learning processes. This study concludes that integrating interactive media designed to support deep learning represents a crucial strategy for strengthening critical thinking skills among elementary school students.